Способ определения оптимальной скорости резания - Нестеренко В. П. Владимир Петрович; Сериков Л. В. Леонид Вениаминович; Арефьев К. П. Константин Петрович; Водопьянов А. В. Анатолий Васильевич; Ульянов В. Л.
опубл. 10.06.01